Piotr Stolypin and the National question in the Russian Empire in 1906-1911: new trends in Russian historiography - Gaidis, Ryšard (Lietuvos istorijos studijos, 2011)
The article covers the research on the contribution of Russian historiography of the last two decades into studying the life, political ideas, and activities of Piotr Stolypin. Attention is focused on the biographical genre and on the issue how the national policy of P. Stolypin and the government under his leadership in the "national outskirts" of the Russian Empire in 1906–1911 is revealed in such type of works.A formal analysis of the Russian historiography of the last two decades, aimed at P. Stolypin and his national policy in 1906–1911, enables to draw a conclusion that the research of biographical nature lacks a closer and broader reflection on P. Stolypin's political plans and steps in all "national outskirts" of the Russian Empire. The collection of subjects and problems, inherited from the Soviet historiography, is reconsidered and reinterpreted, thereby acquiring the form of opposition to the Soviet historiographical tradition.Territorially, the historians research P. Stolypin's actions only in the Western Provinces, the Kingdom of Poland, and the Grand Duchy of Finland. Therefore, the policy of P. Stolypin's government is totally unrevealed in other territories governed by the Russian Empire: the Baltic governorates, the Caucasus, Transcaucasia (South Caucasus), Central Asia, and Bessarabia.Problematically, not the general government policy, but individual, though substantial, aspects thereof, such as introduction of municipalities of Russian governorates and counties (zemstvo), legal restriction of Finnish autonomy, violation of territorial integrity of the Kingdom of Poland, change of the legal status of the Jewish community, consideration of a draft law on confessions are studied in the regions at issue.Thus, both territorially and problematically, the problem is not exhausted as yet and, with reference to hitherto prevailing Russian historiography, we cannot propose a thorough and exhaustive comparative picture of P. Stolypin's national policy in the Russian Empire. Even though the base of sources on this matter is expanding, it is not analyzed by historians in more detail but simply mastered in an uncritical manner.
Keywords: -